Constructing Research Questions: Doing Interesting Research - Alvesson, Mats; Alvesson, Mats (London : SAGE Publications Ltd, 2024)
For any researchers wanting to produce interesting and influential theory development, a key step is formulating innovative research questions. While many traditional textbooks on research methods gloss over ways of constructing research questions, in this text, Alvesson and Sandberg have developed a problematization methodology for identifying and challenging the assumptions underlying existing theories and for generating research questions that can lead to more interesting and influential theories. The second edition of this popular text has been fully updated and: 1. Examines the broader possibilities of doing more reflexive and creative research; 2. Incorporates and critically examines recent ideas about formulating research questions; 3. Is packed full of new examples, including illustrating the different gap-spotting routes for generating research questions; 4. Contains a new empirical study examining the dominance of gap-spotting within social science research; 5. Looks at the complexity of generating research questions; and 6. Includes additional examples of applying the problematization methodology from across the social sciences. Constructing Research Questions is essential reading for students and researchers looking to formulate research questions that are interesting and novel.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business and Management; Communication and Media Studies; Criminology and Criminal Justice